Plan estratégico para la compañía de taxis “TAXS CARDERÓN” de la ciudad de Quito, provincia de Pichincha periodo 2024 - 2029 - Barros Taipe, Anghela Karina (2024)
This project was carried out with the objective of developing a strategic plan for the taxi company TAXS CARDERÓN, since currently its management is empirical, without solid bases. Therefore, this project was conducted with the aim of developing a strategic plan for the aforementioned taxi company. The methodology used includes the analytical, inductive, deductive, and descriptive methods. Techniques such as surveys directed at both internal and external customers, as well as an interview with the company's manager, were applied. The results showed the absence of a strategic plan, mission, vision, and organizational structure, which negatively impacts the company’s long-term operational stability. The weighted score of the EFE matrix, 3.01, suggests that the company responds relatively effectively to external opportunities and threats. Likewise, the EFI matrix demonstrated that the company has more strengths than weaknesses, with a score of 2.58; however, critical areas in need of attention and improvement were identified. The SWOT matrix revealed both strengths, such as user loyalty and a value-driven work environment, as well as critical weaknesses, including the lack of a strategic plan and limited resources for innovation. Based on the diagnosis, a strategic plan was developed, defining the company's mission, vision, and values, as well as its organizational structure. Six strategic objectives were established to improve, grow, and maintain a competitive position in the local market. Additionally, specific strategies were defined for each objective, including goals, policies, tactics, responsibilities, and activities to be carried out. The estimated budget for the implementation of the proposal is $9,410.00.